DETERMINANTS OF LONELINESS, RESILIENCE, AND MENTAL HEALTH IN ELDERLY PATIENTS AT LONG TERM CARE IN JAKARTA : LONELINESS, RESILIENCE, AND MENTAL HEALTH - Andas, Amzal Mortin; Romantika, I Wayan; Silaswati, Shinta; Prima, Ashar; Purnamasari, Anisa; Lisnawati, Lisnawati (STIKes Mandala Waluya Kendari, 2024)
Background: Elderly individuals in nursing homes often experience psychological challenges such as loneliness, decreased resilience, and mental health issues. Understanding the prevalence and determinants of these issues is essential for designing targeted interventions. This study aims to examine the prevalence of loneliness, resilience, and mental health issues among elderly patients at Long Term Care, and to identify the key factors influencing these variables. Methods: A cross-sectional study design was employed involving 126 elderly residents aged 60-90 years. Data were collected using validated instruments, including the UCLA Loneliness Scale, the Resilience Scale, and the General Health Questionnaire (GHQ-12). Demographic and clinical data, such as age, gender, education level, length of stay, marital status, income, and history of chronic diseases, were also recorded. Statistical analyses included descriptive statistics for prevalence and logistic regression to identify significant predictors of loneliness, resilience, and mental health. Results: The prevalence of loneliness was 58%, with a higher incidence among females and those aged over 70 years. Resilience was significantly lower in participants with chronic diseases and lower socioeconomic status. Mental health issues were identified in 45% of participants, with lower education levels, longer stays in the nursing home, and chronic illness as significant contributing factors. Logistic regression revealed that chronic disease history (OR = 3.32, p < 0.05) and length of stay >5 years (OR = 1.91, p < 0.05) were the strongest predictors of poor mental health outcomes. Conclusion: The study highlights the high prevalence of loneliness, reduced resilience, and mental health issues among elderly residents at Long Term Care. Chronic disease and prolonged institutionalization emerged as critical factors influencing psychological well-being. These findings underscore the need for targeted interventions, such as structured psychosocial therapies, to address these challenges and improve the quality of life of elderly patients.